1998
DOI: 10.1152/ajpregu.1998.275.2.r654
|View full text |Cite
|
Sign up to set email alerts
|

Circadian system of mice integrates brief light stimuli

Abstract: Light is the primary sensory stimulus that synchronizes or entrains the internal circadian rhythms of animals to the solar day. In mammals photic entrainment of the circadian pacemaker residing in the suprachiasmatic nuclei is due to the fact that light at certain times of day can phase shift the pacemaker. In this study we show that the circadian system of mice can integrate extremely brief, repeated photic stimuli to produce large phase shifts. A train of 2-ms light pulses delivered as one pulse every 5 or 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 17 publications
4
43
0
Order By: Relevance
“…The rate of decline from the prompt to the sustained drive follows a nonlinear pattern. Our results in humans are consistent with results from animal studies that showed light-induced phase resetting to be most efficient at the beginning of the LE, with minimal additional phase shift produced by further extension of the light stimulus due to a reduction in photic responsiveness of the circadian pacemaker (3,4,8,13). A recent report documents that the number of light-evoked action potentials per photon from intrinsically photosensitive retinal ganglion cells (ipRGCs) that mediate LE-induced phase shifts declines as the duration of the photic stimulus increases (14).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The rate of decline from the prompt to the sustained drive follows a nonlinear pattern. Our results in humans are consistent with results from animal studies that showed light-induced phase resetting to be most efficient at the beginning of the LE, with minimal additional phase shift produced by further extension of the light stimulus due to a reduction in photic responsiveness of the circadian pacemaker (3,4,8,13). A recent report documents that the number of light-evoked action potentials per photon from intrinsically photosensitive retinal ganglion cells (ipRGCs) that mediate LE-induced phase shifts declines as the duration of the photic stimulus increases (14).…”
Section: Discussionsupporting
confidence: 90%
“…More recently, a train of sixty 2-millisecond pulses administered every minute over 60 minutes induced ~45 minutes of phase delay (6,7). Given that the circadian pacemaker can integrate photic signals (3,8), these multiple-exposure studies cannot isolate the phase shift induced by each individual pulse. Mechanistic studies of phase resetting in animals show that the pacemaker can integrate and respond to pulses presented 60 minutes apart (17) and that the majority of a phase-resetting response occurs at the beginning of the light pulse (18)(19)(20).…”
Section: L I N I C a L M E D I C I N Ementioning
confidence: 99%
See 1 more Smart Citation
“…Shorter duration of light exposures in the order of microseconds to milliseconds have been tested in rodents (45)(46)(47). While a single 2-millisecond flash of light is insufficient to phase shift the murine circadian system, a sequence of flashes administered once per minute for 60 minutes is sufficient to evoke phase delays (48). This study by Van Den Pol and colleagues, in addition to other published studies in rodents (45)(46)(47), established that the mammalian circadian system has the capacity to respond to a sequence of very brief, millisecond flashes of light.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted, however, that brief (1 s) light pulses (DeCoursey 1972;Earnest and Turek 1983) or a short series of extremely brief (2 ms), intense light flashes, which are ineffective as single flashes (van den Pol et al 1998;Vidal and Morin 2007) can produce significant phase shifts of the circadian clock. Very brief stimuli do not appear to demonstrate the same type of temporal integration associated with light pulses several minutes in duration (Nelson and Takahashi 1999;Vidal and Morin 2007;Morin et al 2010).…”
Section: Iprgc Response Kineticsmentioning
confidence: 99%